Evaluating the extent of clinical uncertainty among treatment options for patients with early-onset scoliosis - Corona, J.; Miller, D.; Downs, Jennepher; Akbarnia, B.; Betz, R.; Blakemore, L.; Campbell, R.; Flynn, J.; Johnston, C.; McCarthy, R.; Roye, D.; Skaggs, D.; et al. (British Editorial Society of Bone and Joint Surgery, 2013)
Background: Literature guiding the management of early-onset scoliosis consists primarily of studies with a low level of evidence. Evaluation of clinical equipoise (i.e., when there is no known superiority among treatment modalities) allows for prioritization of research efforts. The objective of this study was to evaluate areas of clinical uncertainty among pediatric spine surgeons regarding the treatment of early-onset scoliosis. Methods: Fourteen experienced pediatric spine surgeons participated in semistructured interviews to identify clinical variables that influence decision making in the treatment of early-onset scoliosis. A series of case scenarios of 315 patients with idiopathic and neuromuscular early-onset scoliosis was then developed to be representative of those encountered in clinical practice. Using an online survey, eleven surgeons selected their choice of eight treatment options for each case scenario. Associations between case characteristics and treatment choices were assessed with chi-square and logistic regression analysis. Participants then reviewed the areas of treatment uncertainty identified in the survey, nominated additional research questions of interest, and ranked their interest to further explore the identified research questions.Results: Collective equipoise was identified in numerous scenarios in the survey spanning a range of ages and magnitudes of scoliosis, and additional questions were identified during the nominal group technique. Areas that had the greatest clinical uncertainty included the management of patients who have finished treatment with a growing-rod, timing of rod-lengthening intervals, and indications for spine-based and rib-based proximal instrumentation anchors. The use of rib anchors compared with spine-based anchors was ranked highly for consideration in future clinical trials. Conclusions: Variability in decision making with regard to the optimum treatment of certain subsets of patients with early-onset scoliosis reflects gaps in the available evidence. Structured consensus methods identified priorities for higher levels of research in this area of scoliosis. Higher-level studies, including randomized trials, should focus on answering the questions highlighted in this report.